Art and practice of musical theatre choreography - Abate, Cassie (London [England] : Bloomsbury Methuen Drama, 2022)
"What does a musical theatre choreographer actually do? They just 'make up the steps', right? This book firstly debunks the misunderstandings around what musical theatre choreographers actually do, demonstrating their need to have an in-depth understanding of storytelling, music theory, performance practices and plot structure in order to create movement that enhances and enlivens the musical. Secondly, it equips the musical theatre choreographer with all the tools needed to create nuanced, informed and inspired movement for productions, through structured activities that build specific skills (such as 'notating the script' and 'scoring the score'). Traditionally, this training has been something of a series of secrets, passed from mentor to apprentice. The author demystifies the process to make the previously undisclosed "tricks of the trade" accessible to all choreographers, everywhere. Covering the entire process of choreographing a musical from the first script reading to the final curtain call, this book makea case for the absolute integrity of the choreographer to any musical theatre production and sets out the theoretical principles of choreography alongside the practical application during every step of the production process."--
9.1. Members of the Choreographic Team -- 9.1.1. Dance Captain -- 9.1.2. Assistant Choreographer -- 9.1.3. Associate Choreographer -- 9.2. Pre-Production -- 9.3. Auditions -- 9.3.1. Audition Breakdown -- 9.3.2. Dance Calls -- 9.3.3. Audition Combination -- 9.3.4. In the Room -- 9.3.5. Making the Cut -- 9.4. ACTIVITY: The Dance Audition Combination -- 10. CHAPTER 10: Collaboration -- 10.1. Design and Production Meetings -- 10.1.1. Creative Discussions -- 10.1.2. Design Meetings -- 10.1.3. Break Out Meetings -- 10.1.4. Production Meetings -- 10.2. Collaborating with the Director and Music Director -- 10.2.1. The Director -- 10.2.2. The Music Director -- 10.2.3. The Dance Arranger -- 10.3. Collaborating with the Design Team -- 10.3.1. The Set Designer -- 10.3.2. The Costume Designer -- 10.3.3. The Lighting Designer -- 10.3.4. The Sound Designer -- 10.4. The Stage Manager -- 10.5. The Director/Choreographer -- 10.6. ACTIVITY: Question Lists -- 11. CHAPTER 11: Rehearsals -- 11.1. Types of Rehearsals -- 11.1.1. Staging Rehearsals -- 11.1.2. Cleaning Rehearsals -- 11.1.3. Run-Throughs -- 11.1.4. Spacing Onstage -- 11.1.5. Sitzprobe and Wandelprobe -- 11.1.6. Technical Rehearsals -- 11.1.7. Previews -- 11.2. Running Rehearsals: How to Lead -- 11.2.1. Working with Performers -- 11.2.2. Giving Notes -- 11.3. ACTIVITY: Rehearsal Timeline -- 12. CHAPTER 12: All the Other Things -- 12.1. Transitions -- 12.2. Contact and Intimacy -- 12.3. Improvisation -- 12.4. Child Performers -- 12.5. Special Skills -- 12.6. Curtain Call -- 12.7. Photo Call -- 12.8. Rehearsing Understudies and Swings -- 12.9. Accessibility -- 12.10. Activity: Tracking Transitions -- 13. CHAPTER 13: Nice Work If You Can Get It -- 13.1. Finding Work -- 13.2. Creating Your Own Work -- 13.3. Displaying Your Work -- 13.4. ACTIVITY: Choreography Reel -- APPENDIX: Suggested Reading.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Dance; Choreography; Choreography,Musicals; Electronic books